IMPROVING STUDENTS' ABILITY IN ANALYZING GRAMMATICAL ERRORS IN WRITING THROUGH DISCUSSION GROUPS - Sherly Gaspersz (Bajang Institute, 2022)
The biggest problem found in writing English text is that there are errors in English grammar. Therefore, the effort in this study was carried out with the aim of analyzing errors in English grammar through writing English texts as well as measuring the increase in the ability to analyze writing errors using the group discussion method. This research was conducted using Classroom Action Research (CAR) which is part of the qualitative descriptive method in research using the Kemmis and Mc. Taggart. The object of research in eleventh grade students are fifteen students. Based on the research conducted, the results of the study found three errors in English grammar including: 1) Verbs, 2) To Be, and 3) Personal Pronouns. The errors in the three types of grammar are mostly writing errors, subtraction and even exaggerating words, as well as students' incomprehension in placing grammar in the correct position. Thus the research conducted at the pre-test stage of cycle 1. Cycle and cycle 2 reached the final result, namely 60% of student learning outcomes were in the very high category, which indicates that the minimum completeness standard of e-learning is for students in schools.